IMPLEMENTASI KEBIJAKAN SURAT EDARAN BUPATI SINTANG TENTANG PENGHENTIAN PENGGUNAAN PLASTIK SEKALI PAKAI DAN PENGGANTIAN DENGAN WADAH RAMAH LINGKUNGAN - Mahin, Mikael (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
Abstract: This study discusses the implementation of the Sintang Regent’s Circular Letter policy on the termination of single-use plastic usage and its replacement with environmentally friendly containers. This policy was issued as an effort by the local government to reduce the negative impacts of plastic waste on the environment and public health. The research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the policy to discontinue the use of single-use plastics in Sintang Regency has been carried out, but has not yet been optimal. This is due to a lack of socialization, low public awareness, and limitations in supervision and sanctions. On the other hand, supporting factors include the commitment of the local government and the increasing environmental awareness among some members of the community. It is recommended that the local government enhance continuous socialization efforts, strengthen supervision, and provide incentives to business actors who use environmentally friendly containers in order to support the successful implementation of the policy. Keywords: Policy implementation, single-use plastics, environment.